Vindicating capital: heroes and villains in A Lion's Trail - Havard Ovesen; Adam Haupt (Ilha do Desterro, 2011)
This paper analyses François Verster’s A Lion’s Trail (2002), a documentary about the late musician Solomon Linda andhis hit song, Mbube. Linda died a pauper, despite the fact that his composition became one of the most commerciallysuccessful songs in the history of popular music. Considering the potentially substantial financial benefits due to SolomonLinda’s daughters as heirs to his intellectual property rights, the story of Mbube can easily be read as having a happy, ifsomewhat bittersweet, ending. This ending is remarkably similar to the grand narrative of the new and democraticSouth Africa; in the end, justice was served, although not everybody was around to enjoy it. Such readings, however,obscure certain aspects of the new South African realities. The power structures that enable the continuation of huge socioeconomicdisparities are still in place. We contend that the film’s characertisationof protagonists and antagonists in its narrative as well as the closure that is provided by the actions of Gallo allow viewers to overlook some key problems thatpersist in dominant assumptions about intellectual property, the ill-treatment of countless other black musicians during apartheid, as well as racialised class inequalities that persistnearly two decades after apartheid. The paper will commence with a brief description of Linda’s career in order to set the scene for our analysis of Verster’s documentary. This analysiswill be informed by insights into intellectual property; we will then relate these insights to a discussion of South Africa’sadoption of neo-liberal economic policies. In essence, we argue that, much like the country’s implementation of neoliberalstrategies like Black Economic Empowerment (BEE), the assumptions inherentin A Lion’s Trail about intellectual property vindicate capital and, by implication, the racialised classdivide in post-apartheid South Africa.